Temperature as a Determinant in the Comparative Study of Budde Effect, Joshi Effect and Corona Pressure Effect in Chlorine - Prashad, Jagdish (Asian Journal of Chemistry, 2010)
A comparative study of the Budde effect, Joshi effect and corona pressure effect in chlorine admixed with a little air and water vapour enclosed in the annular space of Siemens type ozonizer has been made in the temperature range 37 to 98°C. Budde effect has been found to be independent in the above temperature range. This has been attributed to the fact that both the characteristic convergence frequency and light absorption in chlorine are practically unaffected by a 61°C temperature rise. And, water acts as a 'poison' by forming an adsorption layer on the wall surface. The Joshi effect and the corona pressure effect have been found to increase in the above temperature range. This is in accord with Joshi's theory for the phenomenon Δi .